Determinant of readiness for adopting healthy lifestyle behavior among university employee: structural equation modeling - Malini, Hema; Sarfika, Rika; Kardila, Intan Yullya; Watterson, Jessica; Saifudin, I Made Moh. Yanuar (Intelektual Pustaka Media Utama, 2025)
Identifying the factors influencing healthy lifestyle behaviors among university faculty and staff is crucial for designing interventions to enhance health outcomes and reduce healthcare expenses. This study aimed to explore the determinants of readiness for adopting healthy lifestyle behaviors among university employees, with a focus on aspects such as diet, physical activity, and stress management in Indonesia. Using a cross-sectional survey approach, respondents participated in guided interviews utilizing the G-form. Through Partial Least Square Structural Equation Modelling (PLS SEM) analysis, it was found that while lifestyle choices did not significantly impact readiness to change lifestyles (p-value>0.05); factors such as health status, use of preventive services, mental health, and perception of occupational health significantly influenced readiness (p-value<0.05). The study underscores the importance of considering various factors, including mental health, health status, and work-related perceptions, to encourage readiness for lifestyle changes among university employees. An incorporating comprehensive wellness programs with mental health resources, regular health screenings, and workplace health initiatives should be considered in implementation of healthy lifestyle program in the universities.